AIDS: voorlichting en preventie - Avonts, D.; Dekeyser, L.; Dumon, W. (Leuven: Federatie van Consultatiebureaus voor Levens- en Gezinsvragen, 1988)
"D. Avonts; L. Dekeyser; W. Dumon... et al. Fonds Suzan Daniel (FSD)"